An investigation of students’ communication skill development: pre and post industrial training - Rodzalan, Shazaitul Azreen; Mohd Arif, Lily Suriani; Mohamed Saat, Maisarah (© Serials Publications, 2016)
This paper reports the development of students’ communication skill development based on industrial training intervention. It also reports the relationship between students’ demographic and students’ communication skill development. A total of 1,227 students completed the pre survey and 485 usable surveys were collected in the post survey. Survey consists of 13 communication items developed based on previous studies. actor analysis conducted has identified underlying two underlying constructs, namely Adjustment and Message. Using paired test, findings reveal that students’ communication skill has developed significantly. The findings show that students significantly developed in both constructs however, they performed better in the Message construct. The findings also show that both male and female students developed significantly in this skill. Malay students were found to develop greater communication skill compared to their non-Malay counterparts. It also appeared that Science and Engineering students developed a highly significant in communication skill. Meanwhile, Social Science students showed no development. The correlation analysis conducted found that there is no relationship between academic performance and students’ communication skill development. The findings of this study provide some practical and educational implications.